A facile chemical route synthesis and characterization of CdSe/ZnO nanocomposite - Das, Isha; Sagadevan, Suresh; Chowdhury, Zaira Zaman; Vijayan, N. (Springer, 2018)
The controlled synthesis of CdSe/ZnO-nanocomposite fabrication by facile chemical route has been successfully performed. Crystalline structure was examined by XRD patterns, while the morphology was investigated was carried out using typical electron microscopic investigations of SEM and HR-TEM equipped with electron dispersion spectroscopy (EDS) analogous to the detection of chemical elements in hybrid composite. The typical SEM image of fabricated CdSe/ZnO-nanomaterial and the grain size was found to 12 nm. The elemental composition of CdSe/ZnO-nanomaterial was analyzed by energy dispersive X-ray spectrometry (EDS). The HR-TEM images of CdSe/ZnO NPs confirm the agglomerated particles neck with their neighbors and form hexagonal shapes. The UV–visible absorption spectroscopy was used to analyze the optical properties. From UV absorption spectrum, a broad peak at 405 nm was observed. The photoluminescence (PL) spectrum was also used to determine the optical properties. The PL spectrum shows the maximum was slightly red-shifted to 625 nm. At various frequencies and at an ambient condition of temperatures, the dielectric studies such as dielectric constant, dielectric loss and AC conductivity properties were investigated. Furthermore, we have studied the current density–voltage of CdSe/ZnO-nanocomposite.